Adaptive Mechanisms of Tumor Therapy Resistance Driven by Tumor Microenvironment - Wu, Peijie; Gao, Wei; Su, Miao; Nice, Edouard C.; Zhang, Wenhui; Lin, Jie; Xie, Na (Frontiers in Cell and Developmental Biology, 2021)
Cancer is a disease which frequently has a poor prognosis. Although multiple therapeutic strategies have been developed for various cancers, including chemotherapy, radiotherapy and immunotherapy, resistance to these treatments frequently impedes the clinical outcomes. Besides the active resistance driven by genetic and epigenetic alterations in tumor cells, the tumor microenvironment (TME) has also been reported to be a crucial regulator in tumorigenesis, progression, and resistance. Here, we propose that the adaptive mechanisms of tumor resistance are closely connected with the tumor microenvironment rather than depending on non-cell-autonomous changes in response to clinical treatment. Although the comprehensive understanding of adaptive mechanisms driven by the tumor microenvironment need further investigation to fully elucidate the mechanisms of tumor therapeutic resistance, many clinical treatments targeting the tumor microenvironment have been successful, In this review, we report on recent advances concerning the molecular events and important factors involved in the tumor microenvironment, particularly focusing on the contributions of the tumor microenvironment to adaptive resistance, and provide insights into potential therapeutic methods or translational medicine targeting the tumor microenvironment to overcome resistance to therapy in clinical treatment.